Knowledge domains and hotspots of the association between hypertension and noise: a bibliometric analysis and visualization study from 2003 to 2023 - Wu, Tianqi; Zhang, Siming; Zhang, Zhou; Pu, Jun; Liu, Ruizi; Yuan, Tianyi; Chen, Xu; He, Songnian; Hao, Qingyu; Gu, Jue (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesNoise pollution has become an increasingly severe environmental issue in modern society and has been recognized for its adverse effects on cardiovascular diseases. Hypertension induced by noise exposure has garnered significant research interest and a large quantity of studies have been conducted. This study aims to employ bibliometric methods to comprehensively review the literature on the relationship between noise exposure and hypertension and to analyze the current state of research by identifying key areas of focus while also exploring future trends in this field.MethodsThe bibliometric analysis was conducted using the Web of Science Core Collection (WoSCC) database. The search query included terms related to noise pollution and hypertension. The timeframe for the search was from 2003 to 2023. Data analysis and visualization were performed using VOSviewer, CiteSpace, Scimago Graphica, and Rtools, focusing on publication trends, citation metrics, explosive intensity, and collaborative networks. Pajek was used to adjust pictures.ResultsThe bibliometric analysis showed a notable rise in research output on the relationship between noise pollution and hypertension. The United States led in the number of publications, with China and Germany coming next. The study identified several key contributors, with Muenzel Thomas being the most prolific author, followed by Daiber Andreas and Pershagen Goran. Institutionally, Johannes Gutenberg University Mainz emerged as the leading institution in terms of publications, followed by Karolinska Institute. Collaborative networks among institutions highlighted significant international cooperation, with extensive collaborations observed, particularly between European and North American institutions. The study also pinpointed research hotspots and emerging trends through keyword analysis. Key areas of focus included the mechanisms linking noise exposure to hypertension, the impact of noise on cardiovascular health, and the role of environmental stressors.ConclusionsThis study advances our understanding of noise-induced hypertension's physiological and biological mechanisms, emphasizing the need for continued research. The research underscores the necessity of addressing noise pollution as a significant public health concern.